The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1104/pp.007468
|View full text |Cite
|
Sign up to set email alerts
|

The COBRA Family of Putative GPI-Anchored Proteins in Arabidopsis. A New Fellowship in Expansion

Abstract: Identification of regulatory molecules that determine the extent and direction of expansion is necessary to understand how cell morphogenesis is controlled in plants. We recently identified COB (COBRA) as a key regulator of the orientation of cell expansion in the root. Analysis of the Arabidopsis genome sequence indicated that COB belongs to a multigene family consisting of 12 members, all predicted to encode glycosylphosphatidylinositol-anchored proteins. All but two of the COBL (COB-like) genes are expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
190
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(205 citation statements)
references
References 53 publications
6
190
1
1
Order By: Relevance
“…We found that COB was undetectable in embryo extracts but present in callus tissue, where levels of COB protein are strongly reduced in pnt1 compared with the wild type. COB is one of an 11-member gene family, several of which are expressed during embryogenesis, and all of which have been either predicted or shown to be GPI anchored (Roudier et al, 2002;Borner et al, 2003). The magnitude of cellulose decrease in cob roots (;30%) is similar to that seen in pnt1 embryos (40%).…”
Section: Importance Of Gaps For Cell Wall Biosynthesissupporting
confidence: 51%
“…We found that COB was undetectable in embryo extracts but present in callus tissue, where levels of COB protein are strongly reduced in pnt1 compared with the wild type. COB is one of an 11-member gene family, several of which are expressed during embryogenesis, and all of which have been either predicted or shown to be GPI anchored (Roudier et al, 2002;Borner et al, 2003). The magnitude of cellulose decrease in cob roots (;30%) is similar to that seen in pnt1 embryos (40%).…”
Section: Importance Of Gaps For Cell Wall Biosynthesissupporting
confidence: 51%
“…In addition, OsBC1L1, OsBC1L5, and OsBC1L8 were characterized by an additional N-terminal region of 170 amino acids (Fig. 1b), which was also found in the Arabidopsis AtCOBL7 subgroup and maize ZmBk2L1 subgroup (Roudier et al 2002;Brady et al 2007). …”
Section: Identification and Sequence Analysis Of The Rice Osbc1l Familymentioning
confidence: 92%
“…The COBRA gene encodes a glycosylphosphatidylinositol (GPI)-anchored protein that has an N-terminal signal sequence for secretion, a hydrophilic middle, a highly hydrophobic C terminus, a CCVS (Cys-rich) motif, an x-attachment site for GPI processing, two putative N-glycosylation sites, and two predicted cellulose binding sites (Roudier et al 2002). COBRA belongs to a multigene superfamily (COBRA-like family), a large protein family only existing in plants (Roudier et al 2002). There are 12 members in Arabidopsis (COBRA, AtCOBL1-11), 11 in rice (BC1, OsBC1Lp1, OsBC1L1-9), and 9 in maize (ZmBK2, ZmBK2L1, ZmBK2L3-9; Roudier et al 2002;Li et al 2003;Brady et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensins and GPI-anchored proteins were not regulated in roots, and only one out of 34 cellulose synthase-related proteins responded to P deficiency in roots, that gene being downregulated. The cellulose synthase-like D1 (Os10g42750), shown to be required for root hair morphogenesis in rice (Kim et al 2007), was not affected by E or G. Based on studies with root-hair-defective Arabidopsis mutants, several additional genes have been linked to root hair development: guanosine triphosphatase (GTPase), glycerophosphoryl-diester-phosphodiesterase-like GPI-anchored protein, and the COBRA-like gene COBL9 (Roudier et al 2002;Hochholdinger et al 2008). In our study, these genes were not differentially regulated by factors E or G.…”
Section: Root Hairsmentioning
confidence: 99%